The Level of Effectiveness of The Utilized Self-Learning Modules (SLMS) in Teaching Science to Senior High School - Jaballa, Jennelyn Ayban (Journal of Research and Investigation in Education, 2023)
Education plays a vital role in contemporary world to succeed. It is important because it is used to alleviate most of the challenges faced in life. This study aimed to determine the level of effectiveness of the utilized self-learning modules in teaching science to Senior High School students in the Schools Division of Zambales. This research paper utilized the quantitative descriptive survey research design. As a master plan specifying the methods and procedures for collection and analyzing the needed information, the descriptive method of research involves the description, of composition or the process of phenomena. The self-learning modules evaluated by the respondents were effective in assessing students’ performance in science. Assessment of the level of effectiveness of the utilized self-learning modules’ was not influenced by the respondents’ Highest Educational Attainment, Area of Specialization, Teaching position, and Length of service in teaching but only by the number of modules writing seminars/training they have attended. There is no significant difference in the level of effectiveness of the utilized SLM when responses are grouped according to learning components, learning goals, and learning competency but there is a significant difference when it comes to the number of trainings they attended.